Quantitative Detection of Escherichia coli O157 in Surface Waters by Using Immunomagnetic Electrochemiluminescence - Shelton, Daniel R. (American Society for Microbiology, 2001)
A protocol for the quantitative detection of Escherichia coli O157 in raw and concentrated surface waters using immunomagnetic electrochemiluminescence (IM-ECL) was developed and optimized. Three antibody sandwich formats were tested: commercial anti-O157:H7 IM beads, IM beads made in-house with a polyclonal anti-O157:H7 immunoglobulin G (IgG), or IM beads made in-house with a monoclonal anti-O157:H7 IgG coupled with a polyclonal anti-O157:H7 IgG to which an electrochemiluminescent label (TAG) was attached. The monoclonal IM bead-polyclonal TAG format was chosen for optimization because it gave lower background levels and linear regression slopes of ca. 1.0, indicative of a constant ECL signal per cell. The dynamic range was ca. 10(1) to 10(5) cells ml(−1) in phosphate-buffered saline and in raw water samples. The monoclonal IM beads selectively captured E. coli O157 cells in the presence of ca. 10(8) cells of a non-O157 strain of E. coli ml(−1). Background ECL signals from concentrated (100-fold) water samples were substantially higher and more variable than raw water samples. The background signal was partially eliminated by the addition of polyvinylpolypyrrolidone. Successive cell capture incubations, termed sequential bead capture (SBC), were optimized for establishing baseline ECL values for individual water samples. The linear dynamic range with SBC was ca. 10(2) to 10(5) E. coli O157 cells ml of concentrated water(−1). To validate the protocol, 10-liter surface water samples were spiked with ca. 5,000 E. coli O157 (Odwalla) cells and concentrated by vortex filtration, and 1- or 3-ml aliquots were analyzed by IM-ECL. Differential ECL signals (SBC) from 1- and 3-ml samples were statistically significant and were generally consistent with standard curves for these cell concentrations. Enrichments were conducted with aliquots of spiked raw water and concentrated water using EC broth and minimal lactose broth (MLB). All tubes with concentrated water became turbid and gave a positive ECL response for E. coli O157 (>10,000 ECL units); MLB gave a somewhat higher detection rate with spiked raw water. The potential sensitivity of the IM-ECL assay is ca. 25 E. coli O157 cells ml of raw water(−1), 25 cells 100 ml of 100-fold concentrated water(−1), or 1 to 2 viable cells liter(−1) with concentration and enrichment. The IM-ECL assay appears suitable for routine analysis and screening of water samples.